Extreme temperature, pressure, and density between 30 and 80 km - Cole, Allen.; Air Force Cambridge Research Laboratories (U.S.)
The distributions of temperatures, pressures, and densities derived from rocket observations between 30 and 80 km are examined with special attention given to extremes. Estimates are provided of the medians and values that are exceeded 1 and 10 percent of the time at various latitudes when the monthly means are highest, and of the 99- and 90-percent extremes and medians when monthly means are lowest. The high and low extreme values of temperature, pressure, and density at these levels occur near the pole. Densities are highest in summer when the circulation pattern is dominated by an anticyclone centered over the pole. Lowest values occur in winter and are associated with the polar cyclone that is normally centered off the east coast of northern Greenland. Research supported by the Air Force Cambridge Research Laboratories, United States Air Force, L.G. Hanscom Field, Bedford, Massachusetts. Aeronomy Laboratory Project 8624. AD0712019 (From http://www.dtic.mil). "12 August 1970." Includes bibliographical references (page 31). The distributions of temperatures, pressures, and densities derived from rocket observations between 30 and 80 km are examined with special attention given to extremes. Estimates are provided of the medians and values that are exceeded 1 and 10 percent of the time at various latitudes when the monthly means are highest, and of the 99- and 90-percent extremes and medians when monthly means are lowest. The high and low extreme values of temperature, pressure, and density at these levels occur near the pole. Densities are highest in summer when the circulation pattern is dominated by an anticyclone centered over the pole. Lowest values occur in winter and are associated with the polar cyclone that is normally centered off the east coast of northern Greenland. Mode of access: Internet.